2022
DOI: 10.28934/jwee22.34.pp46-67
|View full text |Cite
|
Sign up to set email alerts
|

Driving Factors for Women's Switch to Electric Vehicles in Conservative Kuwait

Andri Ottesen,
Sumayya Banna,
Basil Alzougool
et al.

Abstract: Electric Vehicles (EV) is probably the most disruptive and innovative product since the introduction of a smart phone in 2007. However, attitude of women towards (EV) in oil rich and conservative countries like Kuwait has not been explored. The aim of this research is to bridge that gap with this study that employed a quantitative method, that is a questionnaire of 234 women drivers. Results showed that more than half of participated women would buy an EV within the next 3 years, if several conditions were met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…This group favors the soundless engine and lack of maintenance due to its environmental friendliness. The majority of Tesla model Y and model 3 drivers are male, as women in Kuwait are reluctant to purchase vehicles without a dealership [8][9][10][11][12].…”
Section: Resultsmentioning
confidence: 99%
“…This group favors the soundless engine and lack of maintenance due to its environmental friendliness. The majority of Tesla model Y and model 3 drivers are male, as women in Kuwait are reluctant to purchase vehicles without a dealership [8][9][10][11][12].…”
Section: Resultsmentioning
confidence: 99%
“…This study had three goals: (i) to examine Kuwaiti ICE vehicle drivers' indicated perceptions of EV attitudes; (ii) to identify their preferable EV features; (iii) to determine their prospective EV purchase requirements and conditions. This research is part of a larger initiative that examines the EV landscape in Kuwait and utilizes a mixed-methods approach [48].…”
Section: Literature Reviewmentioning
confidence: 99%